Acid denaturation of aspergillus niger glucoamylase and structural transitions induced by various alcohols and polyols / Mohammed Suleiman Mohammed Zaroog - Zaroog, Mohammed Suleiman Mohammed (2013)
Acid denaturation of Aspergillus niger glucoamylase was studied using different conformational probes. Both far-UV CD spectral signal (MRE222nm) and tryptophan fluorescence remained unchanged in the pH range, 7.0–3.0 but decreased significantly below pH 3.0, whereas the ANS fluorescence showed a marked increase below pH 1.5. Maximal changes in the MRE222nm value and the ANS fluorescence were noticed at pH 1.0. The acid-denatured state of glucoamylase at pH 1.0 retained a significant amount of secondary structure as reflected from the far-UV CD spectra but showed a deformed tertiary structure with significant exposure of the nonpolar groups as well as the tryptophan residues as revealed by the increased ANS fluorescence, decreased tryptophan fluorescence and three-dimensional fluorescence spectral signals and increase in the Ksv value in acrylamide quenching experiments. The acid-denatured state showed no significant variation in the CD spectral signal throughout the temperature range, 0-100°C. However, a late cooperative transition was observed upon GdnHCl treatment, compared to the native enzyme. All these results suggested that the acid-denatured state of glucoamylase at pH 1.0 represented the molten globule-like state. Different probes such as far- and near-UV CD spectral signals, ANS binding, Trp fluorescence and three-dimensional fluorescence were used to study halogenol- versus alkanol-induced conformational transitions in the acid-denatured state (pH 1.0) of glucoamylase. These alcohols showed significant retrieval of the protein structure, inducing both secondary and tertiary structural changes, as evident from the increase in the -helical III content and decrease in the ANS binding, respectively. However, halogenols were found more competent than alkanols, requiring lesser alcohol concentration to induce similar spectral change. The effectiveness of these alcohols showed the order: HFIP > TFE > 2-chloroethanol for halogenols while tert-butanol > 1-propanol > 2-propanol > ethanol > methanol for alkanols. Both Trp fluorescence and near-UV CD spectra showed anomalous pattern, though the order of effectiveness remained the same as found with the far-UV CD and ANS fluorescence results. Three-dimensional fluorescence results of the acid-denatured state (pH 1.0) of glucoamylase in the presence of 5.5 M tert-butanol agreed well with the data obtained from the far-UV CD and Trp fluorescence. All these results suggested the formation of partially folded states of glucoamylase in the presence of these alcohols, being more effective with halogenols than alkanols. Different spectral probes such as far-UV CD spectral signal, tryptophan fluorescence and ANS fluorescence were employed to study structural changes and stabilizing effect of various polyols i.e. ethylene glycol, glycerol, glucose and trehalose on the native, the acid-denatured and the thermal-denatured states of glucoamylase. Addition of polyols to the incubation mixture led to significant structural changes involving both secondary and tertiary structures in the acid-denatured state of the enzyme as reflected from the increase in the MRE222nm value and altered tryptophan and ANS fluorescence characteristics. On the other hand, thermodynamic analysis in terms of Tm, ΔHvH and ΔG (25˚C) of the thermal denaturation curves obtained with the native glucoamylase in the presence of various polyols, suggested significant increase in the enzyme stability in the presence of glucose, trehalose and glycerol while ethylene glycol destabilized it. The stabilizing effect was found to be higher with glucose followed by trehalose and minimum IV with glycerol. Furthermore, CD and fluorescence spectral characteristics of the thermal-denatured glucoamylase at 71˚C obtained in the absence and the presence of polyols showed greater effectiveness of both glucose and trehalose in inducing native-like secondary and tertiary structures compared to glycerol and ethylene glycol.